2020
DOI: 10.1016/j.heliyon.2020.e04797
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of geriatric assessment tools for frailty among community elderly

Abstract: Background Frailty is an important condition in elderly individuals because it increases disability, morbidity, and mortality. The definition frailty from the Cardiovascular Health Study (CHS) criteria is used worldwide and defined as fulfilling 3 out of the 5 phenotypic criteria that indicate compromised energetics: weakness, slowness, low level of physical activity, self-reported exhaustion, and unintentional weight loss. Objective This research aims to study the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 44 publications
1
27
0
1
Order By: Relevance
“…Previous studies have shown that the TUG test is a good predictor of frailty identification. A cut-off point of 10 seconds for the TUG test was observed in some studies (Savva et al, 2013, Sukkriang et al, 2020, Ambagtsheer et al, 2020 with sensitivity of 72.0% and specificity of 82.54% obtained by Sukkriang et al, (2020) 2017) suggested a cut-off point of eight seconds, with AUC of 0.775, sensitivity of 85.0%, specificity of 59.5%. Methodological differences, such as sample size and study design, may justify the divergence of the findings.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that the TUG test is a good predictor of frailty identification. A cut-off point of 10 seconds for the TUG test was observed in some studies (Savva et al, 2013, Sukkriang et al, 2020, Ambagtsheer et al, 2020 with sensitivity of 72.0% and specificity of 82.54% obtained by Sukkriang et al, (2020) 2017) suggested a cut-off point of eight seconds, with AUC of 0.775, sensitivity of 85.0%, specificity of 59.5%. Methodological differences, such as sample size and study design, may justify the divergence of the findings.…”
Section: Discussionmentioning
confidence: 86%
“…However, which is the best cut-off point to identify frail older adults is still uncertain. Most studies have cut-off points above 10 seconds for the identification of frail older adults (Savva et al, 2013, Walston, Buta et al, 2018, Sukkriang et al, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the paucity of studies in the Middle East, in general, makes an uncertain assessment of frailty in the Middle East region. More studies are needed examining the net contribution of frailty screening to risk prediction in different settings and populations, and for both clinical and patient-centered outcomes [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The growth in life expectancy in the past decades has led to increasing frailty, which is a risk factor for many diseases [1]. To prevent the associated negative health outcomes, an early identification of the frailty signs and symptoms is needed.…”
Section: Introductionmentioning
confidence: 99%